A broadband coplanar waveguide to WR4 contactless transition using interdigital‐pin electromagnetic bandgap structure. Issue 5 (8th February 2022) - Zhang, Qing; Yao, Yuan; Cheng, Xiaohe; Xiu, Tao; Yu, Junsheng; Chen, Xiaodong
Abstract: A broadband coplanar‐to‐rectangular waveguide transition using contactless electromagnetic bandgap (EBG) structure in the form of interdigital‐pin bed of nails has been introduced in this paper. The electromagnetic (EM) wave propagates from the CPW, and then radiates from the probe into the WR4. The rectangular patch is adopted as the probe to accomplish a broadband performance without an impedance transformer. At the same time, CPW to rectangular waveguide (RW) directly transition without EBG unit also has been designed and the simulated results show the transmission performance has low tolerance to air gap. The interdigital‐pin EBG structure is added to the machining splitter of the RW which is no need for strict electrical contact and is not harmful for transition performance. The greatest advantage of the interdigital‐pin lattice has a significant pin gap increase and is easy to fabricate for millimeter‐wave (mm‐Wave) and terahertz (THz) applications. The back‐to‐back prototype is designed, fabricated and measured. The measured | S 11 | is better than −10 dB over 170–260 GHz, covering a bandwidth of 41.8%.